Seminar Sistem Pendistribusian Tenaga Listrik Dari Pembangkit Sampai Konsumen di SMK Swasta Istiqlal Deli Tua - Lisa Adriana Siregar; Yussa Ananda; Agus Almi Nasution (LPPM STIKOM Tunas Bangsa, 2022)
In the field of electricity, it is necessary to convey to students that the sources of electricity have many types, both conventional energy and new renewable energy that can be managed by consumers with small power capacities. With this information, it becomes one of the supporters of students' curiosity about electrical concepts used in everyday life. Many students do not know about small-scale electrical systems in residential homes, do not know the distribution of electricity to consumers, do not know the distribution from the generator to the network, and do not know the equipment that helps in distribution to consumers. The PKM team helps high school students understand electricity, and explains the basics of electricity, electricity distribution, and power generation through videos and slides. The PKM team helps high school students understand electricity, explains the basics of electricity, electricity distribution, and power generation through videos and slides the PKM team helps high school students understand electricity, explains the basics of electricity, electricity distribution, and power generation through videos and slides the PKM team helps high school students understand electricity, explains the basics of electricity, distribution of electricity, and internal power generation through videos and slides. Based on the results of monitoring and evaluation, in general, they are able to understand and are enthusiastic to know, as can be seen from the questions that are weighty so that not all questions are answered due to time constraints. So that the committee promised in the future the duration of the time will be extended.